Lean system design framework based on lean functionalities and criteria integration in production machines design phase - Slim Rabih (University of Belgrade - Faculty of Mechanical Engineering, Belgrade, 2021)
Manufacturing needs more and more requirements (sustainability, agility, Industry 4.0 technologies, etc.) to meet customer demands. Nowadays, companies apply Lean tools to improve machines and systems performance in their use phase. Lean tools application on existing machines ensures some functionalities like (Reduce changeover time, eliminate wastes, Involve Human Skills, etc.). The purpose of this paper is to offer designers a design support method and tool to design a performant system (production system, machines, etc.) by integrating Lean functionalities from the early design phases, with a minimum of needs to improve the system in the use phase via Lean. For this purpose, we analyze the Lean principles and tools to identify functionalities provided by Lean. These functionalities are analyzed and classified to integrate them into the design of manufacturing systems in the context of Industry 4.0. A "Lean-System-Design" approach defines a systematic and detailed guide for the integration of Lean from the early design phase. We provide the software tool specifications, which represent the first steps of its implementation. We have illustrated our proposal with a case study on the design of a waste treatment machine.